The future of food business : the facts, the impacts, the acts - Neves, Marcos Fava (World Scientific, 2011)
This unique book is a collection of articles published by the author in leading newspapers around the world. The papers focus on food chains and new concepts and ideas on how to increase competitiveness and value within the food and agricultural sectors. The book gives a comprehensive description of the food chain and suggests methods and tools that can be used by companies to re-structure their innovative market strategies. It discusses up-to-date trends, world food crises, integrated food chains and strategic planning for companies in the food sector. It also covers international investments.